2021
DOI: 10.1186/s12905-021-01350-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone levels in females of different ages suffering from depression

Abstract: Background There are only a few studies on sex hormones in females of different ages suffering from depression, and their conclusions are not uniform until now. This study aimed to investigate the correlation between the severity of depression in females and factors such as sex hormones and differences in sex hormone levels in females of different ages, exploring variations after treatment. Methods A total of 169 females with depression were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…57 However, significantly higher levels of E2 were reported in perimenopausal women with first episode of depression compared to those with recurrent depression. 58 In contrast, a clinical trial study conducted to assess the antidepressant response to ketamine found no differences between men and women; however, the sample size was small and the outcome was focused on the response to a single treatment. 59 In addition, the authors did not take into account the timing of the menstrual cycle and the use of contraceptives, which may be vital when assessing the influence of gonadal hormones on the response to ketamine.…”
Section: Potential Determinants Of Variability In the Pharmacodynamic...mentioning
confidence: 98%
See 1 more Smart Citation
“…57 However, significantly higher levels of E2 were reported in perimenopausal women with first episode of depression compared to those with recurrent depression. 58 In contrast, a clinical trial study conducted to assess the antidepressant response to ketamine found no differences between men and women; however, the sample size was small and the outcome was focused on the response to a single treatment. 59 In addition, the authors did not take into account the timing of the menstrual cycle and the use of contraceptives, which may be vital when assessing the influence of gonadal hormones on the response to ketamine.…”
Section: Potential Determinants Of Variability In the Pharmacodynamic...mentioning
confidence: 98%
“…Glutamate based therapy has been proposed for treatment of perimenopausal depression 57 . However, significantly higher levels of E2 were reported in perimenopausal women with first episode of depression compared to those with recurrent depression 58 . In contrast, a clinical trial study conducted to assess the antidepressant response to ketamine found no differences between men and women; however, the sample size was small and the outcome was focused on the response to a single treatment 59 .…”
Section: Potential Determinants Of Variability In the Pharmacodynamic...mentioning
confidence: 99%
“… 35 In turn, fluctuation in estrogen levels in women is one of the proposed mechanisms of a higher incidence of depression in women. 36 Lei et al 37 reported that estrogen levels were substantially lower in patients with recurrent depression compared with patients with first-episode depression. Whether disrupted homeostasis of estrogen in women with depression is associated with increased risk for AF development remains an area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…This can be because the measuring instruments used in the study are also different. 9,13,14,15 The clinical picture due to decreased estrogen levels is very complex, influenced by organobiological, psychological and socio-cultural aspects. From the organobiological point of view, symptom manifestations occur in organs that require these hormones.…”
Section: Menopause Relationship With Depression Levelsmentioning
confidence: 99%